2013
DOI: 10.1515/pterid-2013-0018
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase inhibitors for thoracic tumors

Abstract: AbstractThymidylate synthase (TS) is a valid target for treatment of non-small cell lung cancer (NSCLC) and mesothelioma (MPM). The TS inhibitor pemetrexed (PMX) is now commonly used in combination with cisplatin (CDDP) or carboplatin, in the first-line setting for both of these lethal diseases. A combination of another TS inhibitor, Tomudex with CDDP, demonstrated similar activity in MPM patients. However, the efficacy of TS inhibitors is limited by uptake, metabolism and targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…13 CB3717, pemetrexed, raltitrexed and plevitrexed are quinazoline based folic acid TS inhibitors for the treatment of various cancers. 14 Previous studies have reported that incorporation of different heterocycles in the skeleton has shown significant inhibition of TS. For example, derivatives containing pyrimidine-indole, 15,16 N -phenyl-(2,4-dihydroxy pyrimidine-5-sulfonamido)phenyl urea, 17 pyrrolo-pyrimidine, 18–20 cyanopyrimidine, 21 benzothiazole, 22 phenolnaphthalein 23 and thiouracil 24 displayed promising inhibition of TS.…”
Section: Introductionmentioning
confidence: 99%
“…13 CB3717, pemetrexed, raltitrexed and plevitrexed are quinazoline based folic acid TS inhibitors for the treatment of various cancers. 14 Previous studies have reported that incorporation of different heterocycles in the skeleton has shown significant inhibition of TS. For example, derivatives containing pyrimidine-indole, 15,16 N -phenyl-(2,4-dihydroxy pyrimidine-5-sulfonamido)phenyl urea, 17 pyrrolo-pyrimidine, 18–20 cyanopyrimidine, 21 benzothiazole, 22 phenolnaphthalein 23 and thiouracil 24 displayed promising inhibition of TS.…”
Section: Introductionmentioning
confidence: 99%